2012
DOI: 10.1111/j.1095-8649.2012.03292.x
|View full text |Cite
|
Sign up to set email alerts
|

Age and growth of albacoreThunnus alalungain the North Pacific Ocean

Abstract: The age and growth of North Pacific albacore Thunnus alalunga were investigated using obliquely sectioned sagittal otoliths from samples of 126 females and 148 males. Otolith edge analysis indicated that the identified annulus in a sagittal otolith is primarily formed during the period from September to February. The assessments of the fish age at first annulus formation indicated that the first annulus represents an age of <1 year. This study presents an age estimate (0·75 years) for the formation of the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…() example, discussion of sampling issues is often insufficient (e.g., Chen et al. ; Gervelis and Natanson ; Dunton et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…() example, discussion of sampling issues is often insufficient (e.g., Chen et al. ; Gervelis and Natanson ; Dunton et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Males appear to grow faster and larger than females in most or all tuna species (e.g. albacore, Williams et al, 2012;Chen et al, 2012;bigeye, Farley et al, 2006;southern bluefin, Farley et al, 2014a,b). Billfish sex dimorphism is more pronounced, with females growing considerably faster and larger than males (e.g.…”
Section: Sex-specific Growth Ratesmentioning
confidence: 97%
“…LOTI has most significant fitness with albacore tuna stock trajectory in Zone 1, Zone 2 and Zone 3 with a lag of t − 1 year ( Table 3). Albacore tuna in the Pacific Ocean recruit to surface fisheries when they are about 2 years old and while age at catch ranges from 1 to 15 years, most of the stock is harvested when the stock is between 2 and 4 years old [23]- [25]. Ramon and Bailey [38] have shown that spawning by mature albacore tuna takes place in the South Pacific tropical and subtropical latitude band from 10˚S to 25˚S and the recruitment of the juveniles occurs after one year at around 40˚S in New Zealand waters.…”
Section: Discussionmentioning
confidence: 99%
“…Monthly and annual L, P and O were tested against Y z1 , Y z2 , and Y z3 at t − n years where 0,1, , 5 n =  since the age of most of the stock harvested in the Pacific Ocean ranges between 2 -4 years old [23]- [25]. Results with p < 0.05 were considered as significant relationships.…”
Section: Exploratory Analysis and Unit Root Testmentioning
confidence: 99%